A CASE STUDY ON THE STRATEGY OF DEVELOPING THE ATTRACTION OF '4A' AS A CULTURAL TOURISM AT THE CENTER FOR NATIONAL ARCHIVES STUDIES JAKARTA - Gracia Pratama Wijaya; Vishnuvardhana S. Soeprapto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
The National Archives Building is a symbol of Jakarta's history. The National Archives building was once used as an orphanage and church. As the name suggests, the National Archives Building previously functioned as a document warehouse. The function of the National Archives Building began around the 1800s during the Dutch East Indies government. The original name of the National Archives Building was Villa Molenvliet. To find out, the Archives Study Center for the first President of the Republic of Indonesia, Ir. Soekarno, consists of 4 halls, namely: Hall 1 Aku Indonesia, this hall tells the story of Sukarno from birth to death. Hall 2 Jalan Politics This hall depicts Sukarno as a political giant. Hall 3 Cultural Patrons This hall explains that apart from being an accomplished politician, Sukarno also loved beauty. Hall 4 Welfare and Democracy This hall tells the story of one of Sukarno's leaderships, which was to improve the welfare of the people, which was done by nationalizing the nation's assets. This research uses descriptive qualitative field research methods. The research results show that regarding attractiveness, it can be seen that the National Archives Study Center is still lacking in facilities and accessibility. By adding several existing deficiencies to meet visitor needs.